State-of-Art Functional Biomaterials for Tissue Engineering - Sharma, Krati; Mujawar, Mubarak A.; Kaushik, Ajeet (Frontiers in Materials, 2019)
Nano-bio-technology-enabled tissue engineering strategies have emerged as an innovative and promising technique in the field of regenerative medical science. The design and development of multi-functional smart bio-materials compatible to human physiology is crucial to achieving the required biological function with a reduced negative biological response. Several medical bio-implants have been tested to boost life expectancy and better-quality life. The concept of biocompatibility focusses on body acceptance and no harmful effects after implantation which require shaping the properties of materials synthesis, surface functionalization, and bio-functionality. Such developed bioactive and biodegradable materials have been utilized to achieve the required function at a specific period and sustainability to withstand the surrounding tissues for treating severe injuries and diseases. Thus, exploring new approaches to design multifunctional biocompatible advanced nanostructure to develop next-generation therapies for tissue engineering, this mini-review is an attempt to summarize the advancements in bio-functional smart materials. The review focuses on bio-mimic materials, bio-materials, self-assembly bio-materials, bio-printing functional hydrogels, new polymeric architectures, and hybrid synthetic-natural hydrogels in the field of tissue engineering and regenerative medicine (TERM). This mini-review will serve as a guideline to design future research where the selection of a smart multi-functional bio-material is crucial to obtain best TERM performance.